Research on Taylor Vortex and Heat Transfer in AxialRadial Cooling Motor - LU Yiping; DONG Shanshan; ZHAO Bomin; HAN Jiade; GE Yajun (Journal of Harbin University of Science and Technology)
The analysis of flow and transfer of heat in the air gap of synchronous motor associated with axial-radial ventilation system is important due to the complexity of flow of cooling air in the air gap between rotor and stator. A physical model is established according to the cooling air ducts which comprises of air gap, stator and rotor of the synchronous motor Based on the finite volume method, only the rotation of rotor wall, flow and heat transfer in a concentric annular air gap space is simulated numerically The gradual increase of three factors i.e. the outflow of radial cooling of stator air duct, axial flow of cooling air in the air gap, rotor air duct out flow and the influence of Taylor vortex flow and heat transfer characteristics in the air gap are analyzed.The result shows that the axial flow of inlet air strongly affects the flow and convective heat transfer of stator and rotor in the air gap and provides a reference for the design of synchronous motor associated with axialradial ventilation system.